The effect of alpha lipoic acid on rat kidneys in methotrexate induced oxidative injury - (:unkn) unknown (VERDUCI PUBLISHER, 2015)
OBJECTIVE: The purpose of this study is to determine the antioxidant and anti-inflammatory effects of alpha lipoic acid (ALA) on methotrexate (MTX) induced kidney injury in rats. MATERIALS AND METHODS: Thirty-two rats were equally divided into four groups; control, ALA, MTX and MTX with ALA groups. A single dose of MTX (20 mg/kg) was administered to make kidney injury to groups 3 and 4, intraperitoneally. The ALA was administered intraperitonealy in groups 2 and 4 and the other groups received saline injection for five days. On the sixth day the blood samples and kidney tissues were obtained for the measurement of TNF-alpha, IL-1 beta, malondialdehyde, glutathione, myeloperoxidase and sodium potassium-adenosine triphosphatase levels and histological examination. RESULTS: Administration of MTX caused a decrease in tissue GSH, and Na+, K+-ATPase activity significantly. A significant increase in tissue MDA and MPO activities were also seen. The pro-inflammatory cytokines (TNF-alpha, IL-beta) were increased in the MTX group significantly. ALA treatment reversed all biochemical indices as well as histopathological alterations induced by MTX administration. CONCLUSIONS: MTX made oxidative damage on kidneys of rat and it was partially prevented by anti-inflammatory and antioxidant effects of ALA treatment.
Keywords: Alpha lipoic acid; Methotrexate; Kidney; Oxidative injury; HIGH-DOSE METHOTREXATE; TOXICITY; STRESS; MYELOPEROXIDASE; MELATONIN; RELEASE